Patient characteristics and outcome measurement in a low secure forensic hospital - Longdon, Laura; Edworthy, Rachel; Resnick, Jeremy; Byrne, Adrian; Clarke, Martin; Cheung, Natalie; Khalifa, Najat (John Wiley & Sons, Ltd, 2018)
Background: Health services are increasingly required to measure outcomes after treatment, which can be reported to the funding body and may be scrutinised by the public. Extensive high quality measurements are time consuming. Routinely collected clinical data might, if anonymised, provide good enough evidence of useful change consequent on service received. Research question: Do the Health of the Nation Scale (HoNOS) and the 20 item Historical, Clinical, Risk (HCR-20) structured professional judgement tool scores provide evidence of clinical and risk change among low security hospital patients at 6 and 12 months after admission? Methods: One hundred and eight men were either resident on the unit on1st January 2011 or new admissions to the census date of 31st May 2013. Their routinely collected data were added to an outcome register following each patient’s Care Programme Approach clinical review meeting and analysed using repeated measures t-tests with Bonferroni corrections. Results: Most of the men, mean age 34.3 years, were single (93%), White British (71%) and with a primary diagnosis of schizophrenia (62%). There were significant reductions in the 11-item HoNOS (excluding the community living condition scale) scores between baseline and 6 months, and between 6 months and 12 months, but no change on its additional 7-item secure subscale. Individual effect sizes indicated that 39% of the men had better social function, although 18% had deteriorated at six months. There was little overall change in the HCR-20; individual effect sizes indicated that 11 men (15%) were rated as being at lower risk level and 10 (14%) at higher after six months in the study. Conclusions/implications for clinical practice: Standard clinical measures are promising as indicators of change in low security hospital patients. Risk ratings may be conservative, but, at this stage of a secure hospital admission, higher scores may be as likely to indicate progress in identifying and quantifying risks as apparent increase in risk.